To see or not to see (again): Dealbreakers and dealmakers in relation to social inclusion - Jonason, Peter K.; White, Kaitlyn P.; Lowder, Abigail H.; Al-Shawaf, Laith (Frontiers in Psychology, 2022)
In this study we replicated what is known about the relative importance of dealbreakers (i.e., traits avoided) and dealmakers (i.e., traits sought) in romantic and sexual relationships and extended it to an examination of self-reports of mate value, self-esteem, and loneliness. In two experiments (N = 306; N = 304) we manipulated the information people were told about potential partners and asked them about their intentions to have sex again with or go on a second date with opposite sex targets. People were less interested in partners after learning dealbreakers, effects which operated more strongly in the long-term than short-term context, but similarly in men and women. People who reported less self-esteem or more loneliness were more receptive to people with dealbreakers. People who thought they had more mate value, more self-esteem, or less loneliness were more receptive to dealmakers. Results are discussed using sociometer, prospect, and sexual strategies theories.